Analysis of the land use sector in INDCs of relevant Non-Annex I parties - Yvonne Hargita; Sebastian Rüter (Johann Heinrich von Thünen-Institut, 2016)
The international community has committed itself to adopt a global climate agreement in Paris in 2015, which shall enter into force in 2020 and shall be legally-binding for all. In advance of the negotiations, parties shall submit the so-called Intended Nationally Determined Contributions (INDC), providing the voluntary national emission reduction pledges post 2020. For the purposes of 14 of the Lima Call for Climate Action parties may also provide information on whether and in what manner removals are taken into account. Removals are synonymous for the land use (LU) sector that can serve as a carbon sink or source, depending on the national preconditions and the sector's management. Climate negotiations in the past have shown that the accounting rules that result from the special role of the LU sector have a major impact on the accounting of emissions and removals (in the sum: net-removals), and thus on the pledged overall emission reduction targets. Since the international community has yet not been able to agree on binding accounting rules for post-2020, every party can decide on its own, how it considers net-emissions from LU in its INDC. Countries with large forest areas could significantly weaken their overall level of ambition by applying national profitable rules. With our analysis of the LU sector in relevant Non-Annex I-INDCs, we critically reflect the potential role of forests and the REDD+ mechanism for the national reduction targets. The analysis shows that the assessed parties have taken advantage of the missing common rules and designed their reduction targets in a variety of ways. This variety risks transparency, completeness and comparability of information and complicates the assessment of ambition. The remaining issues that could not be answered with the data provided confirmed the need for independent technical review of emission data and assumptions behind future emission development by UNFCCC experts. These reviews could assure that the quality of pursuing negotiations of reduction targets would not be compromised. At the present state, the inclusion of the LU sector and its impact on future reduction commitments remain a source of uncertainty. – – Die internationale Staatengemeinschaft hat im Dezember 2015 in Paris ein globales Klimaabkommen verabschiedet, welches ab 2020 in Kraft treten und alle Mitgliedstaaten zu verbindlichen Emissionsreduktionen verpflichten soll. Im Vorlauf der Verhandlungen wurden von den Staaten nationale Emissionsreduktionsbeiträge für post 2020 eingereicht, die sogenannten Intended Nationally Determined Contributions (INDC). Im Sinne des 14 des Lima Call for Climate Action sollen die INDCs unter anderem Auskunft darüber geben, ob und auf welche Weise Kohlenstoffeinbindungen im Landnutzungssektor berücksichtigt werden. Die Verhandlungen unter dem Kyoto Protokoll in der Vergangenheit haben gezeigt, dass der Landnutzungssektor eine besondere Rolle spielt, da die Anrechnungsregeln einen entscheidenden Einfluss auf die Berücksichtigung von Emissionen und Einbindungen haben können. Da sich die Staatengemeinschaft bisher nicht auf verbindliche Anrechnungsregeln unter einem gemeinsamen Klimaabkommen einigen konnte, haben die Länder derzeit alle Freiheiten bei der Ausgestaltung ihrer freiwilligen Reduktionziele. Insbesondere der potentielle Beitrag des Landnutzungssektors, der je nach natürlichen Voraussetzungen und Nutzung als Treibhausgasquelle oder -senke fungieren kann, stellt eine Unsicherheit hinsichtlich der über alle Staaten akkumulierten Emissionsreduktionsziele dar. Mit unseren INDC-Analysen relevanter Non-Annex I-Länder für den Landnutzungssektor, haben wir die potentielle Rolle von Wäldern und REDD+ für die jeweiligen nationalen Reduktionsziele kritisch hinterfragt. Es hat sich gezeigt, dass die untersuchten Länder die Freiheiten in der Anrechnung nutzen, und im bestehenden Rahmen unterschiedlichste Ansätze auswählen. Diese Vielfalt geht auf Kosten von Transparenz, Vollständigkeit und Vergleichbarkeit der Emissionsziele und erschwert die Bewertung des Ambitionsniveaus. So bleiben Fragen offen zu Emissionsdaten und zu Annahmen zukünftiger Emissionsentwicklungen. Die Auswertung der INDCs zeigt, dass eine unabhängige Überprüfung der INDC-Datenlage durch UNFCCC-Experten notwendig ist, um die Rolle des Landnutzungssektors für künftige globale Emissionsreduktionsziele in den weiteren Verhandlungen einschätzen zu können. Zum jetzigen Zeitpunkt bleibt die Berücksichtigung des Landnutzungssektors in einem zukünftigen Klimaregime eine Quelle für Unsicherheiten.
urn:nbn:de:gbv:253-201511-dn055903-4
Keywords: 630; Paris Agreement; forest; land use; Brazil; India; Indonesia; UNFCCC; INDC; Non-Annex I; REDD+; 2020; 2030; Pariser Klimaabkommen; Wald; Landnutzung; Brasilien; Indien; China; Indonesien